Characteristics of different mesh types for abdominal wall repair in an experimental model of peritonitis. Issue 13 (13th September 2017) - Kaufmann, R.; Jairam, A. P.; Mulder, I. M.; Wu, Z.; Verhelst, J.; Vennix, S.; Giesen, L. J. X.; Clahsen‐van Groningen, M. C.; Jeekel, J.; Lange, J. F.
Abstract : Background: The use of synthetic mesh to repair a potentially contaminated incisional hernia may lead to higher failure rates. A biological mesh might be considered, but little is known about long‐term results. Both biological and synthetic meshes were investigated in an experimental model of peritonitis to assess their characteristics in vivo . Methods: Male Wistar rats were randomized into five groups and peritonitis was induced. A mesh was implanted after 24 h. Five meshes were investigated: Permacol™ (cross‐linked collagen), Strattice™ (non‐cross‐linked collagen), XCM Biologic ® (non‐cross‐linked collagen), Omyra ® Mesh (condensed polytetrafluoroethylene) and Parietene™ (polypropylene). The rats were killed after either 30, 90 or 180 days. Incorporation and shrinkage of the mesh, adhesion coverage, strength of adhesions and histology were analysed. Results: Of 135 rats randomized, 18 died from peritonitis. Some 180 days after implantation, both XCM Biologic ® and Permacol™ had significantly better incorporation than Strattice™ ( P = 0·003 and P = 0·009 respectively). Strattice™ had significantly fewer adhesions than XCM Biologic ® ( P = 0·001) and Permacol™ ( P = 0·020). Thirty days after implantation, Permacol™ had significantly stronger adhesions than Strattice™ ( P < 0·001). Shrinkage was most prominent in XCM Biologic ®, but no significant difference was found compared with the other meshes. Histological analysis revealed marked differences in foreign body response among all meshes. Conclusion: This experimental study suggested that XCM Biologic ® was superior in terms of incorporation, macroscopic mesh infection, and histological parameters such as collagen deposition and neovascularization. There must be sufficient overlap of mesh during placement, as XCM Biologic ® showed a high rate of shrinkage. Surgical relevance The use of synthetic mesh to repair a potentially contaminated incisional hernia is not supported unequivocally, and may lead to a higher failure rate. A biological mesh might be considered as an alternative. There are few long‐term studies, as these meshes are expensive and rarely used. This study evaluated the use of biological mesh in a contaminated environment, and investigated whether there is an ideal mesh. A new non‐cross‐linked biological mesh (XCM Biologic ® ) was evaluated in this experiment. The new non‐cross‐linked biological mesh XCM Biologic ® performed best and may be useful in patients with a potentially contaminated incisional hernia. Abstract : Variable characteristics